Experiences of COVID-19 dedicated ward nurse managers in South Korea: a qualitative study - Yoon, Rosa; Gu, Minkyung; Park, Mira; Sok, Sohyune (Frontiers in Public Health, 2025)
BackgroundThe outbreak of new infectious diseases is on the rise worldwide. In particular, hospital nurses and nursing managers responding to the COVID-19 pandemic are facing overwhelming workloads amidst confusion and anxiety. In South Korea, qualitative research exploring the experiences of nurse managers in COVID-19 dedicated wards are needed to strengthen their capacity and develop response strategies.ObjectiveThis study aimed to comprehensively understand and explore the experiences of nurse managers in COVID-19 wards.MethodsA qualitative study using the phenomenological research method of Giorgi was employed. Participants were 12 nurse managers who had been performing nursing care in a dedicated ward for the treatment of COVID-19 patients for more than 1 month and had at least 2 years of experience as a COVID-19 nursing unit manager at general hospitals. They were randomly assigned to two groups of six participants for focus group interviews, and they were in-depth interviewed until data saturation. Data were collected from April to July, 2022.ResultsThe duration of experience as nurse managers in COVID-19 dedicated wards was an average of 7 years and 5 months. The duration of experience as staff nurses in COVID-19 wards was an average of 1 year and 2 months. The five themes derived from this study were ‘the opening of unprecedented COVID-19 dedicated wards’, ‘difficulties in personnel management’, ‘overall predicaments as managers’, ‘demonstrating leadership with responsibility’, and ‘pride in overcoming hardships’. Also, eleven sub-themes were derived.ConclusionNurse managers in COVID-19 dedicated wards need to establish rules and guidelines within the ward to prevent and reduce confusion. They also need to collaborate with hospital administrators to ensure that staff nurses assigned to COVID-19 dedicated wards receive relevant training and are assigned accordingly. Intervention programs for COVID-19 dedicated ward nurse managers need to be developed and implemented. Policymakers need to develop government-level policies and systems to establish a medical support system for hospitals operating COVID-19 dedicated wards.